Impacts of Orthognathic Surgery on Patient Satisfaction, Overall Quality of Life, and Oral Health-Related Quality of Life: A Systematic Literature Review - Rodrigo Zamboni; Flávio Renato Reis de Moura; Myrian Camara Brew; Elken Gomes Rivaldo; Marcylene Arruda Braz; Eduardo Grossmann; Caren Serra Bavaresco (International Journal of Dentistry)
Several treatments have been suggested to correct dentofacial abnormalities, including orthognathic surgery. The aim of the present systematic review was to assess the impact of orthognathic surgery on patient satisfaction, overall quality of life, quality of life related to oral health—and to orthognathic surgery in particular—among adult patients. Two investigators independently reviewed the available literature in the databases PubMed/MEDLINE, LILACS, SciELO, EMBASE, Trip, and Google Scholar (gray literature) based on the keywords “orthognathic surgery” and “quality of life.” An analysis of bias was performed based on the MINORS (methodological index for nonrandomized studies). A total of 245 relevant studies were retrieved from the databases, and 6 additional studies were located after a manual search of the references. Following selection based on titles, abstracts, and full-text analysis, 30 studies were included in the present systematic review. To evaluate quality of life before and after orthognathic surgery, 12 studies applied the surgery-related Orthognathic Quality of Life Questionnaire (OQLQ), 12 used the Oral Health Impact Profile (OHIP-14), and 4 used the Short Form Health Survey (SF-36). Orthognathic surgery results in improvements in quality of life both physically and psychosocially after surgery and is associated with high rates of patient satisfaction.